2019
DOI: 10.1074/mcp.ra118.000988
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Hidden Components of the Chloroplast Envelope Proteome: Opportunities and Limits of Better MS Sensitivity

Abstract: By quantitatively comparing the proteomes of total leaf (crude cell extract) from Arabidopsis and purified chloroplast envelope fractions, this study makes available a novel parameter (calculated Enrichment Factor) for each putative envelope protein. This parameter provides important information to enable the more confident identification of genuine envelope components, distinguishing them from contaminants from other cellular/chloroplast compartments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 90 publications
(164 reference statements)
5
58
0
Order By: Relevance
“…Thus, FBN3a (At3g26070), FBN3b (At3g26080), FBN6 (At5g19940), FBNlike (At1g18060), and probably FBN9 (At4g00030) were found to be thylakoid-localized, FBN5 (At5g09820) and a truncated version of FBN7a (At3g58010) are located in the chloroplast stroma, and FBN10 (At1g51110) in thylakoids and plastoglobules. Furthermore, FBN6 is the only isoform that was found to be enriched in purified envelope fractions (Ferro et al, 2010;Bouchnak et al, 2019). Furthermore, FBN6 is the only isoform that was found to be enriched in purified envelope fractions (Ferro et al, 2010;Bouchnak et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Thus, FBN3a (At3g26070), FBN3b (At3g26080), FBN6 (At5g19940), FBNlike (At1g18060), and probably FBN9 (At4g00030) were found to be thylakoid-localized, FBN5 (At5g09820) and a truncated version of FBN7a (At3g58010) are located in the chloroplast stroma, and FBN10 (At1g51110) in thylakoids and plastoglobules. Furthermore, FBN6 is the only isoform that was found to be enriched in purified envelope fractions (Ferro et al, 2010;Bouchnak et al, 2019). Furthermore, FBN6 is the only isoform that was found to be enriched in purified envelope fractions (Ferro et al, 2010;Bouchnak et al, 2019).…”
Section: Introductionmentioning
confidence: 94%
“…FBN6 is localized to thylakoid and envelope membranes FBN6, together with FBN3a, FBN3b, FBN-like, and most probably FBN9, was found to be thylakoid localized (Lundquist et al, 2012). Moreover, FBN6 is the only FBN isoform that was found to be enriched in purified envelope fractions (Ferro et al, 2010), a localization that was recently supported by Bouchnak et al (2019). To experimentally test for the subcellular location of FBN6, the fluorescence distribution in Col-0 protoplasts overexpressing the FBN6-eGFP fusion was investigated.…”
Section: Photosynthetic Properties Of Fbn6-1 Mutant Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…CDC48 functions in a variety of cellular activities beyond protein homeostasis, such as cell cycle regulation and autophagy, but it is especially well known as the core motor component in ERAD [118]. Of the five reported homologues of CDC48 in Arabidopsis, CDC48A was found to associate with Toc33 [114], and has recently been identified by proteomic analysis of the chloroplast envelope [119]. Reconstitution experiments demonstrated that CDC48 operates as a cytosolic motor to retrotranslocate ubiquitinated TOC proteins prior to their degradation, a process in which SP2 was also shown to be critical [114] (Figure 1).…”
Section: Chloroplast-associated Protein Degradationmentioning
confidence: 99%
“…(ii) More than 100 nucleus-encoded transporters or transporter components were detected in comparable amounts of PM samples showing that our method is feasible to detect this group of proteins. (iii) IM transporters were repeatedly identified in comparable analyses of cyanobacterial(43)(44)(45)(46)(47) or plastidial membrane fractions(48)(49)(50). Thus, a mechanism to insert nucleus-encoded multi-spanning TM proteins into chromatophore IM and thylakoids likely has not evolved (yet) in P. chromatophora.…”
mentioning
confidence: 99%